Does SEA change outcomes? - Mario R. Partidário (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
This paper addresses the advocacy role that SEA can strategically play towards more sustainable and environmental decision-making and how this can be achieved. It discusses the required conditions for this performance and also the frustrations of SEA when such conditions are absent or insufficient. The paper shares the experience with the case of an SEA on the strategic decision on the location of the new international airport in Lisbon, particularly with respect to how SEA made a difference to infrastructure development decisions and the conditions that were met to make it possible.
Keywords: 330